Faktor Penyebab Balita Stunting Pada Awal 1000 Hari Pertama Kehidupan (Studi Kualitatif Di Puskesmas X) - Mardhiah, Himmatun (Jurnal Khazanah Intelektual, 2025)
Background: Stunting is a state of growth failure due to chronic malnutrition since the first 1000 days of life, so that toddlers are too short for their age. Stunting is the cumulative result of a process that begins during pregnancy, problems when pregnant women become the cause of stunting in toddlers. Some of the problems that occur in pregnant women such as lack of nutritional intake, teenage pregnancy, history of hypertension, and depression. Purpose: To gain an in-depth understanding of the causes of stunting in toddlers starting in the early first 1000 days of life period in the X Health Center area. Methods: This study used a qualitative description. Data collection is done by with an in-depth interview approach. Informants were selected by purposive sampling. The informants consisted of 5 people, 1 key informant (nutrition officer) and 4 informants of mothers who have stunted toddlers. The research tools used were interview guides and recorders. Results: the causes of stunting in the early first 1000 days of life period at the X Health Center occurred due to factors from direct and indirect causes. Direct causal factors include teenage pregnancy, nutritional intake during pregnancy, history of hypertension and depression during pregnancy. In addition, there are also indirect causal factors for stunting which include knowledge and family income. Conclusion: The causes of stunting in the early first 1000 days of life period include teenage pregnancy, nutritional intake during pregnancy, history of hypertension, depression during pregnancy. knowledge and family income.